Pengaruh Operasional Bus Sarana Angkutan Umum Massal (SAUM) Penurunan Kemacetan di Kota Balikpapan - Muhammad Hadid; Dwiana Novianti Tufail; Hera Widyastuti (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Implementing bus as a public transport system could reduce traffic congestion on urban roads. This study aims to identify the effectiveness of Sarana Angkutan Umum Massal (SAUM) bus in congestion reduction in Balikpapan. This study uses a macroscopic approach to analyze the changing in traffic characteristics when SAUM buses operate. Modal shift percentage is gained from the previous study. The focus of traffic characteristics is the degree of saturation, operational speed, and travel time. The result shows that decreasing the degree of saturation, increasing operational speed, and shorter travel time occurred. However, the result also found that operating buses do not contribute significantly to increasing operational speed on low-traffic corridors.